Area of maximum efficiencies of different attractant (1-octen-3-0l, ammonium, acetone, L-lactic acid and dry ice)in forest habitat - Vignjević, Goran (2011)
CDC traps were used to determine the effectiveness and range of used attractants (1-octen-3-ol, ammonium, acetone and L-lactic acid) and their differences in forest habitat (plant community Carpino betuli - Quereetum roboris). Central CDC trap was set as a source of the attractants (Ck). Around it, two circles of CDC traps without attractants were placed. First circle was constituted of 6 CDC traps(distance A) ; while in the second circle there were 12 CDC traps (distance B). Three combinations of circles were used with different A/B distances: 25/50, 35/70 and 45/90 meters. Distance changes between the distance A and distance B from the central trap (Ck) were used for determination of maximum range of the attractants (1-octen-3-ol, ammonium, acetone and L-lactic acid). Dispersions of the attractants were influenced by wind direction and speed, which, including all meteorological factors, had a direct impact on the scattering. Maximum range of the attractants varied greatly. Acetone had lowest effectiveness with maximum range of 35 meters, followed by ammonium with 45 meters and lactic acid with 50 meters. Attractants with longest range are 1-octen-3-ol and dry ice with maximum range of 90 and 110 meters respectively. By measuring the density of mosquitoes at certain distances from the source, we calculated the area of maximum effectiveness for each attractant. All attractants have shown the greatest efficiency at a distance of 45 m from the source, except dry ice which has showed much greater efficiency at a distance of 70 m from the source. Although the maximum range of attractants during this study varied greatly (35-110 m), area of their greatest efficiency is at 45m from the source of attractant aside from dry ice, whose distance is significantly higher (70m).